Relationship between Sports Motivation and Mindfulness among College Sports Players in Pakistan - Najam-us- Sahar; Rabia Javed (Universitas Ahmad Dahlan, 2018)
The present study aims to determine the association between motivation & mindfulness among college sports players by examining types of motivation from most self determined (intrinsic motivation) to lowest self determined (amotivation) & its relation to dispositional mindfulness. A total of 120 college sports players served as participants (90 boys & 30 girls). They filled Sports Motivation Scale & Mindfulness Attention Awareness Scale with some demographic information. The demographic characteristics revealed that most of participants were in team sports (80%) & playing for last 1-5 years (86%). A significant relationship was found between Intrinsic motivation & mindfulness (r = .70**). Regression analysis showed that intrinsic &integrated regulations were significantly predicting mindfulness (63% variance). It is interesting to know that in Pakistani colleges more boys participate in sports even in absence of facilities (coach is available to 35% of participants only). Self regulation & intrinsic motivation can be utilized to promote the well-being of youth with limited resources available.